Effect of different seed priming methods on seed germination and vigor of okra - Singh, Rashmishree; Kandel, Khumananda (Journal of Agriculture and Natural Resources, 2025)
Okra (Abelmoschus esculentus L.) faces problems of poor germination because of its hard seed coat that restricts water uptake. Seed priming provides a pre-sowing, effective and low-cost technique to enhance germination and seedling vigor. The purpose of this study was to evaluate the effect of different seed priming methods on the germination and vigor of okra variety ‘Arka Anamika’ under laboratory conditions. This study was conducted in a simple Completely Randomized Design (CRD) with three replications and seven treatments (distilled water hydro-priming, 5% cow urine, 200 ppm GA₃, 10% Trichoderma viride, 10% Pseudomonas fluorescens, 5% NaCl, and an untreated control) from 30 May to 14 June 2024. The parameters measured were germination percentage, germination rate, mean germination time, germination speed index, germination energy, seedling vigor index, root & shoot length and allometric coefficient. Treatments differed significantly from one another. GA₃ priming maintained the maximum germination speed index (61.25), germination energy (74.16%), seedling vigor index (1326.33), and shoot length (24.27 cm) while the highest germination percentage (88.66%) and comparable vigor performance were recorded by Trichoderma viride priming. Cow urine was found to be least effective, although hydro-priming yielded a moderate improvement. The findings of this study suggest that the okra seed primed with 200 ppm GA₃ or 10% Trichoderma viride show better performance in terms of seedling vigor and germination under laboratory conditions.